Twenty-five years later: revisiting the challenges to social justice - Chancer, Lynn S. (Social justice, 1999)
Part of a special issue celebrating 25 years of this journal. The writer reflects upon the challenges that exist to social justice 25 years after the first publication of this journal. She concentrates on three aspects of debate, writing, and research: the resuscitation of a tradition of public intellectuality, both inside and outside the world of academic writing; the reconnection of criminology to political economy; and the incorporation of the study of culture and unconscious social processes in to the heart of criminological enterprise. She concludes that criminological investigations highlight possibilities for radical and critical criminology to have a greater impact on public policies.